Carbonated alkali-activated olivine with glass fiber for soil stabilization - Khalaf, Wisam Dhey Ab (2018)
Soil stabilization is a universal approach commonly used in counter-balancing of soil ground under structures. This method of soil improvement utilizes binders such as cement and/or lime to enhance the mechanical properties of soil for construction purposes. However, the production of these binders has been known to increase the levels of carbon dioxide (CO2) in the environment. Therefore, in an attempt to stabilize soil conditions, the search for sustainable materials which are essentially harmless to surrounding soils when treated and at the same time are cost-efficient, is justified. Olivine, with a chemical composition of [(Mg,Fe)2SiO4] can be considered as a sustainable material which has the natural capability of capturing CO2 in the environment and creating carbonated minerals. The high amount of magnesium oxide (MgO) and aluminum oxide (Al2O3), as well as an adequate amount of silicon dioxide (SiO2) form the chemical composition of olivine, making olivine a good choice for use in soil improvement activities in terms of its pozzolanic reaction and hydration. The present study was undertaken to emphasize some problems on the utilization of olivine as a newly proposed sustainable material for soil improvement programs. The study highlights the applicability of glass fiber with an alkali activated soil-olivine mixture, with and without carbonation, which helps in determining the Unconfined Compressive Strength (UCS), Indirect Tensile Strength (ITS), and the Flexural Strength (FS). In the study, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Energy-Dispersive X- ray spectroscopy (EDX), and X-ray Diffraction (XRD) analyses were also executed on pure soil and alkali activated soil-olivine mixtures with and without carbonation. The first stage was to analyze the performance of the preliminary investigation in order to evaluate the effectiveness of olivine on some basic geotechnical characteristics of silty clay soil. The compaction test and the Unconfined Compression Strength (UCS) were used as a practical indicator to investigate the strength development. According to the test findings, utilizing 30% olivine resulted in a sharp increase in the compaction and the UCS of the samples, in the same curing time. In the second stage of this study, carbonated alkaline activation of soil+30% olivine, was adopted as a viable technique to evaluate binder formation due to CO2 pressure change. In simpler terms, the binder formation is generally a synthetic alkali aluminosilicate which is produced from the reaction of a solid aluminosilicate with pre-designed concentrated aqueous alkaline solutes. After this, pressurized CO2 is injected into it form the new binder (MgCO3/CaCO3). Based on the obtained UCS values at exposure pressure of up to 300 kPa, for a 7 day exposure period, using alkali-activated olivine, it was found that the peak strength of soil+30%olivine was increased by up to 55 times compared to that of host soil. Regarding exposure period, it was found that based on UCS results at an exposure period of up to 7 days, using alkali activated olivine, the peak strength of soil+30%olivine was increased by up to 55 times compared to that of host soil.